English Lecturers' Difficulties in Teaching English for Specific Purposes (ESP) in Various Higher Education in Indonesia - Fitria, Tira Nur (Journal of English Teaching and Learning Issues, 2023)
This research investigates the English lecturers’ difficulties in teaching English for Specific Purposes (ESP) in higher education. This research is descriptive qualitative. There are 58 English lecturers from various higher education involved in this research. The analysis shows that the most dominant English lecturers teach ESP in the 2nd semester. Besides, in the 1st, and 3rd semesters. English skills taught by English lecturers in ESP courses are speaking, writing, reading, speaking, vocabulary, and translation. Speaking skills is the difficult English skill taught by them in the ESP course. The most dominant English lecturers have been teaching ESP for more than 5 years. They state that teaching ESP requires more challenges than teaching EGP (English for General Purposes). In the implementation of teaching ESP, they face several difficulties including) 1) making syllabi and lesson plans. 2) making ESP course materials according to student needs. 3) selecting and using learning methods. 4) getting ESP textbooks related to student needs. 5) making/creating ESP textbooks related to student needs. 6) difference in students' English proficiency levels. 7) difference in the level of student's motivation to learn English. 8) different levels of students' awareness of the importance of ESP. 9) the institution’s policy related to the ESP course curriculum has not been clearly stated. 10) institutional policies related to facility policies are not adequate. 11) the number of lectures/credits, and the number of semesters in the ESP course are not as expected. 12) compensation (income) in teaching ESP courses is not expected.